Spatio-Temporal Analysis of Landslide Distribution and Its Impacts in Nepal - Sitaula, Ravi; Sharma, Puspa; Chidi, Chhabi Lal; Acharya, Sangam (The Geographic Base, 2023)
Landslides pose a significant threat globally Nepal located in the Himalayas, exhibits diverse climatic zones and experiences a considerable amount of rainfall during the monsoon season. Landslide occurrences in Nepal are frequent, attributed to active seismotectonic activities, a fragile landscape, and land use practices. The spatial distribution of rainfall in Nepal varies by season due to the influence of different atmospheric phenomena. The study investigates the temporal and spatial patterns of rainfall-induced landslides in Nepal, over the past two decades with a specific focus on the impact of extreme precipitation events. Spearman rank correlation is employed to analyze monotonic relationship between the frequency of landslide incidents with the severity of impact. The results reveal an increasing trend in the number of landslide events and associated fatalities in Nepal, with a nonlinear relationship between events and deaths. Central Nepal experiences the highest concentration of deaths due to factors such as population growth, rural-urban migration, rapid urbanization, and haphazard road construction, particularly in rural areas. Furthermore, compared to the Tarai region and the mountains, the number of fatalities is higher in the hills.